Tren dan Tantangan Keamanan Bertransaksi dengan Qris dalam Era Transformasi Sistem Pembayaran Digital - Desy Natalia Kristanty (Jurnal Syntax Admiration, 2024)
In the current era of digital payment system transformation, the use of Quick Response Code Indonesian Standard (QRIS) has become one of the main trends in the ease of financial transactions. This research aims to explore the trends and challenges faced in transaction security using QRIS. This study uses qualitative research methods and analyzes literature, identifying various aspects of the use of QRIS, including its advantages in imitating digital payment systems. The results of the study show that by implementing advanced data encryption and transaction authentication, QRIS has significantly improved transaction security. In addition, this system encourages the growth of the digital ecosystem and financial inclusion by making it easier to integrate various payment platforms. Although QRIS helps prevent fraud with a verification mechanism and surveillance of suspicious actions, there are still problems. One of them is the need to educate users about security practices. In addition, QRIS has provided a strong foundation for the development of new technologies, encouraging innovation in digital payment systems. When various stakeholders in the payments ecosystem work together, the user experience becomes better. Although innovation has many advantages, the management of new technologies and compliance with safety standards are still a problem. Overall, QRIS offers a secure and integrated payment solution while allowing for innovation. To maximize the benefits of QRIS, all parties must continue to improve their understanding of security, support financial inclusion, and adapt to the latest innovations.